Sedimentology, facies architecture and sequence stratigraphy of a Mississippian age, black mudstone succession -- the upper member of the Bakken Formation, North Dakota, U.S.A. - Borcovsky, Damien A., author; Egenhoff, Sven, advisor; Harry, Dennis, committee member; von Fischer, Joseph, committee member; Fishman, Neil, committee member (Colorado State University. Libraries, 2013)
The early Mississippian age, upper member of the Bakken Formation in the North Dakota portion of the Williston Basin consists of a succession of organic-rich, black siliciclastic mudstones deposited offshore on a low-gradient ramp or shelf. Based on ichnological and sedimentological characteristics twelve fine-grained facies are recognized within the succession and these are grouped into five reoccurring facies associations. Very fine-grained, massive to faintly laminated mudstone (FA1) records deposition in the deepest, calmest parts of the offshore environment, whereas well laminated mudstones (FA2a), well laminated clay clast-bearing mudstones (FA2b), burrow-mottled mudstone with shells (FA3), and interlaminated siltstone and mudstone (FA4) contain sedimentological evidence that argues for deposition in the shallower, less calm, and generally more proximal parts of the offshore environment. These proximal-offshore mudstones (FA2a, FA2b, FA3, and FA4) reflect (1) variation in overall bottom water oxygen levels from dysoxic to possibly as high as oxic, and (2) lateral variation in the input of silt and clay clasts along the basin margin. Ubiquitous Phycosiphon incertum fecal strings throughout the succession along with patches of small shells and centimeter-scale burrows, and rare agglutinated foraminifera indicate that the upper Bakken member was likely deposited primarily in dysoxic to suboxic basinal conditions, and not within a persistently stratified, anoxic environment. In all facies associations, storm event laminae deposited by bedload processes range from sparse to ubiquitous. Repeated stacking of facies associations, which reflect different offshore energy regimes define up to ten coarsening-upward parasequences mostly 0.15-0.60 m thick. These are bounded by flooding surfaces that can be correlated laterally for at least 300 km through the basin, delimiting individual parasequences. Distinct formation-scale facies changes indicate that the lower half of the succession, herein termed Interval 1, represents the distal expression of a transgressive systems tract and was characterized by high radiolaria productivity with minor silt input during higher order sea level lowstands. The upper half of the succession, herein termed Interval 2 represents the distal expression of the base of a highstand systems tract. In contrast to Interval 1, the Interval 2 mudstones are generally characterized by high clay content, low radiolaria productivity, and intermittent colonization of the sea floor by bivalves and millimeter to centimeter-scale burrowing organisms during higher order sea level lowstands. Core descriptions, radiolaria distribution patterns, x-ray diffraction data and comparisons to other shale plays in the United States of America suggest that mature mudstones in the Interval 1 part of the succession outside of the depocenter, and in isolated silt-rich sub-basins, might be sufficiently brittle and permeable to exploit for hydrocarbons utilizing horizontal drilling and hydraulic fracturing technologies.
Zip file contains appendixes 1, 2, and 3.